The Fluid Envelope of our Planet : How the Study of Ocean Currents Became a Science - Mills, Eric L., 1936- (Book collections on Project MUSE., 2009)
A detailed and beautifully written account of the history of oceanography, The Fluid Envelope of Our Planet is an engaging account of the emergence of a scientific discipline.